Spatial navigation impairment is proportional to right hippocampal volume - Nedelska, Zuzana; Andel, Ross; Laczó, Jan; Vlcek, Kamil; Horinek, Daniel; Lisy, Jiri; Sheardova, Katerina; Bures, Jan; Hort, Jakub (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Cognitive deficits in older adults attributable to Alzheimer's disease (AD) pathology are featured early on by hippocampal impairment. Among these individuals, deterioration in spatial navigation, manifested by poor hippocampus-dependent allocentric navigation, may occur well before the clinical onset of dementia. Our aim was to determine whether allocentric spatial navigation impairment would be proportional to right hippocampal volume loss irrespective of general brain atrophy. We also contrasted the respective spatial navigation scores of the real-space human Morris water maze with its corresponding 2D computer version. We included 42 cognitively impaired patients with either amnestic mild cognitive impairment (n = 23) or mild and moderate AD (n = 19), and 14 cognitively intact older controls. All participants underwent 1.5T MRI brain scanning with subsequent automatic measurement of the total brain and hippocampal (right and left) volumes. Allocentric spatial navigation was tested in the real-space version of the human Morris water maze and in its corresponding computer version. Participants used two navigational cues to locate an invisible goal independent of the start position. We found that smaller right hippocampal volume was associated with poorer navigation performance in both the real-space (β = -0.62, P < 0.001) and virtual (β = -0.43, P = 0.026) versions, controlling for demographic variables, total brain and left hippocampal volumes. In subsequent analyses, the results were significant in cognitively impaired (P ≤ 0.05) but not in cognitively healthy (P > 0.59) subjects. The respective real-space and virtual scores strongly correlated with each other. Our findings indicate that the right hippocampus plays a critical role in allocentric navigation, particularly when cognitive impairment is present.
Keywords: Magnetic Resonance Imaging; Hippocampus; Humans; hipokampus; studie případů a kontrol; Case-Control Studies; lidé; magnetická rezonanční tomografie